Peran Kemudahan, Keamanan, Inovasi, dan Kecepatan Layanan terhadap Pengalaman dan Loyalitas Pelanggan pada Aplikasi Fintech Investasi - Lilhaq, Ahmad Ghazy; Salehudin, Imam (Jurnal Manajemen dan Usahawan Indonesia, 2024)
The Role of Ease of Use, Security, Innovation, and Service Speed in Shaping Customer Experience and Loyalty in Investment Fintech Apps This study examines the influence of customer experience on user loyalty toward investment fintech applications in Indonesia. The rapid growth of fintech has revolutionized the financial sector by providing easier and more efficient access to financial services. This research investigates factors influencing customer experience, including ease of use, perceived value, customer support, perceived risk, service speed, and perceived innovativeness, as well as their impact on customer loyalty. Data were collected from 301 users of investment fintech applications in Indonesia and analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). Results indicate that ease of use, perceived value, security, speed, and firm innovativeness significantly affect customer experience. Furthermore, customer experience significantly enhances loyalty intention. These findings offer insights for fintech companies to improve service quality and strengthen customer relationships.